The impact of recurrent abdominal pain: predictors of outcome in a large population cohort. - Ramchandani, P; Fazel, M; Stein, A; Wiles, N; Hotopf, M (2007)
AIM: Recurrent abdominal pain is one of the commonest complaints of childhood, affecting approximately 10% of children at any one time. This study aims to describe the outcome of recurrent abdominal pain amongst 6-year-old children, and to identify risk factors (in both the children and their parents), which predict these outcomes. METHODS: 7128 6-year-old children in the Avon Longitudinal Study of Parents and Children (ALSPAC) were followed up for 1 year. The principle outcomes were abdominal pain, number of days missed from school in the preceding year and psychiatric diagnoses. RESULTS: Children with recurrent abdominal pain at age 6 years had higher rates of further abdominal pain [odds ratio 4.88 (95% CI: 4.01, 5.95)], school absence (10 or more days off school in a year) [OR 1.89 (1.53, 2.33)] and anxiety disorders [OR 2.36 (1.68, 3.32)] at age 7 years. Maternal anxiety was the most consistent predictor of subsequent adverse outcomes for these children. CONCLUSION: Children with recurrent abdominal pain are at significant and continuing risk of adverse functioning. It is important for clinicians to take a whole family perspective, and particularly to consider parental anxiety, when a child with recurrent abdominal pain presents to them.